# Answer to Question #2841 in Algebra for Keyla

Question #2841

Simplify each expression by rewriting it as a single logarithm...

<br>2 log a-3 log b=

<br>

x ln m+ y ln n=

<br>2 log a-3 log b=

<br>

x ln m+ y ln n=

Expert's answer

2 log a - 3 log b = log a

x ln m + y ln n = ln (x

^{2}/b^{3}x ln m + y ln n = ln (x

^{m}y^{n})Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment